Transformasi Pendidikan Holistik Upaya Mengembangkan Keterampilan Abad 21 untuk Menghadapi Tantangan Era Digital - Aufia Aisa; M. Thoriqul Aziz (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is motivated by the limited research on holistic education in developing 21st-century skills to address the challenges of the digital era, despite its significant implications for future human resource quality. The objective of this research is to explore the concept of holistic education based on 21st-century skills and its relevance in the digital era through a literature review approach. The method employed is qualitative, focusing on an analysis of academic literature, including documents, journals, books, and various scholarly sources. The analysis was conducted thematically to investigate the principles, models, and practices of holistic education that support the development of critical thinking, creativity, communication, and collaboration skills. The findings indicate that holistic education can serve as a key approach to prepare younger generations to navigate the complexity of the digital era with adaptive, ethical, and innovative thinking skills. This review enriches the literature on holistic education and highlights the importance of an integrated approach that intertwines cognitive, emotional, social, and technological dimensions within the context of modern learning. Practical implications include recommendations for educators and policymakers to design curricula based on 21st-century skills and integrate digital technologies into building holistic learning processes. This study also offers opportunities for further research on the implementation of holistic education in diverse cultural and geographical contexts.